Method for improving quality of fluorozirconate-silane film of cold-rolled sheet

By systematically controlling multiple factors on the surface of the cold-rolled plate, the quality and corrosion resistance of the fluorozirconate-silane film are improved, and the problems of low quality and corrosion resistance of the fluorozirconate-silane film in the prior art are solved, thereby achieving the energy-saving and environmentally friendly and efficient protection of the process.

CN119876552APending Publication Date: 2025-04-25BAOTOU IRON & STEEL (GROUP) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510070343.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The fluorozirconate-silane film of the prior art cold rolled automotive plate has low quality and corrosion resistance, and the process has high energy consumption and high pollution.

Method used

By controlling the flame cleaning thickness, surface residues, roughness, oil coating amount, fluorozirconate-silanization time interval, surface defects and the number of oxide inclusions on the surface of the cold-rolled plate, a systematic process flow is formulated to improve the quality of the fluorozirconate-silane film.

Benefits of technology

The uniform thickness, dense structure and good corrosion resistance of the cold-rolled plate fluorozirconate-silane film are achieved, which reduces the energy consumption and pollution of the process, and improves the adhesion and corrosion resistance of the electrophoretic paint film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876552A_ABST
    Figure CN119876552A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the quality of a fluorozirconate-silane film of a cold-rolled sheet. The aspects of removal of oxides on the surface of a casting blank, control of surface residues in a cold rolling state, the type of a produced working roll, surface microstructure characterization parameters, the oil coating amount, the time interval from oil coating to fluorozirconate-silanization, surface defect and corrosion point control, the number and area of oxide inclusions, the degreasing effect and the like are standardized; the steel plate surface quality is improved. The invention aims to comprehensively consider various factors influencing the quality of the fluorozirconate-silane film on the surface of the cold-rolled sheet and improve the quality of the fluorozirconate-silane film on the surface of the cold-rolled sheet, and aims to solve the technical problems of low quality and corrosion resistance of the fluorozirconate-silane film on the surface of the cold-rolled sheet at present.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material surface treatment, and in particular relates to a method for improving the quality of a cold-rolled plate fluorozirconate-silane film. Background Art

[0002] The corrosion protection of automobile bodies is mainly achieved through painting. Therefore, painting is an important aspect of automobile body manufacturing process, and the quality of painting directly affects the corrosion resistance and decorative performance of the automobile body. During the painting process, a series of complex chemical reactions occur on the surface of the body material. Phosphating treatment, as an important pre-painting treatment method, aims to form a uniform and dense phosphating film on the surface of the steel plate, thereby improving the surface corrosion resistance and enhancing the adhesion of the primer. It has been widely used in the field of automobile production.

[0003] In the automotive coating industry, the phosphating process has been used for the longest time, and a relatively complete phosphating film quality evaluation system has been formed. However, it has disadvantages such as long process flow, high equipment maintenance cost, and difficult treatment of wastewater and waste residue. For example, the phosphating solution is an acidic solution with a pH value of 3-4, which can easily corrode equipment. The phosphating process is energy-intensive and polluting. The average heat energy consumption is 5 times that of silane treatment, and the sewage treatment cost is 8 times that of silane treatment.

[0004] With the emphasis on environmental protection and energy conservation, surface pretreatment technology is developing towards low cost, low energy consumption and environmental friendliness. Silanization treatment technology is one of the metal surface treatment technologies that meets environmental protection needs. It has the advantages of simple operation, energy conservation and environmental protection, and good bonding with organic coatings and metals. The single silane film layer is thin and prone to defects such as micropores and microcracks. The protective effect on the substrate is limited, which limits the wide application of silane film and requires modification of the silane film. The silane film modified by fluorozirconate has the characteristics of dense film layer and good corrosion resistance. It is one of the steel plate surface treatment processes that has been studied and applied more. Silane film is the link between the steel plate and the electrophoretic paint film. The zirconium oxide doped in the silane film produces a metal bond with the steel plate surface on the one hand, and on the other hand, as a polymer, the silane film can be interwoven with the polymer electrophoretic paint to form a strong physical bond, so that the steel plate and the electrophoretic paint are firmly combined, and the adhesion and corrosion resistance between the electrophoretic paint film and the steel plate are enhanced.

[0005] Compared with the phosphating film, the fluorozirconate-silane film is thinner and has higher requirements on the surface condition of the cold-rolled sheet.

[0006] Patent CN105420607A discloses a control method for improving the paintability and surface quality of cold-rolled automobile sheets. The paintability of cold-rolled automobile sheets is improved by controlling the element distribution, oxidation state and surface roughness of the cold-rolled automobile sheets, and focuses on the control of the production process.

[0007] Patent CN111647733A discloses a method for improving the phosphating performance of low-carbon aluminum-killed steel automobile plates, automobile plates, which improves the surface quality of steel plates by controlling the composition of ingots, hot rolling, cold rolling, annealing and leveling processes.

[0008] The amount can improve the phosphating performance of low carbon aluminum killed steel automobile sheet.

[0009] Patent CN114231822A discloses a method for improving the paintability of the surface of cold-rolled automobile plates. Through smelting, rolling, continuous annealing, pickling, surface conditioning and phosphating processes, the phosphating film layer on the surface of the cold-rolled automobile plate prepared has a dense structure, uniform crystallization, and is granular. The average grain size is 2-3μm, the porosity is small, and it has high paintability.

[0010] The paper "Research Progress of Silane Membrane Technology for Automotive Coating Pretreatment" analyzes in detail the key factors affecting its performance, proposes a structural optimization strategy, and studies the silane agent parameters including the pH value of the silane agent,

[0011] The effects of treatment time, treatment temperature, silane agent concentration and ratio on the quality of silane film, as well as the surface state of the steel plate, such as surface defect repair, element segregation, surface profile, surface freshness, surface oil film cleanability and other influencing factors on the quality of the silane film. Most of the influencing factors are not quantified, but mostly descriptive language.

[0012] The paper "The Influence of Surface Quality of Cold-Rolled Steel Plates on the Performance of Zirconium Films" studies in detail the effects of different roughness, oil coating amounts, element enrichment levels and color difference defects on the surface zirconium film, but there is less research on other influencing factors.

[0013] In summary, the patents and papers on improving the phosphating and silanizing properties of cold-rolled sheets mentioned above have their own advantages and disadvantages, but there are few reports on patents for fluorozirconate-silane films. At the same time, the effects of flame cleaning thickness, the number and size of oxide inclusions, etc. on the quality of fluorozirconate-silane films on the surface of cold-rolled sheets are not comprehensively considered. Summary of the invention

[0014] The purpose of the present invention is to provide a method for improving the quality of fluorozirconate-silane film on cold-rolled sheet, the purpose is to analyze the surface oil coating amount, the time interval from production to fluorozirconate-silanization, surface roughness, peak density, skewness, and surface defect control, comprehensively consider various factors affecting the quality of fluorozirconate-silane film on the surface of cold-rolled sheet, improve the quality of fluorozirconate-silane film on the surface of cold-rolled sheet, and the technical problems to be solved are the current low quality and corrosion resistance of fluorozirconate-silane film of cold-rolled automotive sheet.

[0015] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0016] The present invention provides a method for improving the quality of a cold-rolled sheet fluorozirconate-silane film, comprising:

[0017] Used for flame cleaning of the surface of continuous casting billet for cold-rolled automobile steel and then heating in furnace. The flame cleaning thickness is 4.0-6.0cm. The total amount of residue on the surface of cold-rolled cold-hardened strip after pickling is ≤200mg / m 2 , chrome-plated rollers are used for annealing and leveling;

[0018] Surface morphology characteristic parameters of cold-rolled automotive steel: roughness Ra is 0.7-1.1μm, peak density RPc value is 90-140, surface maximum profile peak height Sp is 2.5-3.5μm, while ensuring that the skewness Ssk is -0.6-0.2, the steepness Sku is 1.5-2.5, the root mean square slope Sdq is 0.35-0.40, the surface area growth rate Sdr% is 4.0-5.5, the surface area ratio is ≥1.05, and the strip surface oil coating amount is 600-1000mg / m 2 ;

[0019] The time interval from oiling to fluorozirconate-silanization is ≤ 50 days;

[0020] Before fluorozirconate-silanization, the surface of the cold-rolled sheet was checked to find no scratches or rust spots visible to the naked eye within an area of ​​70 cm × 150 cm;

[0021] The surface of the cold-rolled sheet was examined by scanning electron microscopy before fluorozirconate-silanization. Within an area of ​​70 cm × 150 cm, the number of oxide inclusions was ≤ 5, and the inclusion area was ≤ 5 × 5 μm. 2 ;

[0022] Before fluorozirconate-silane, sufficient degreasing is carried out to ensure that the surface of the cold-rolled plate is completely exposed and the water film is fully covered.

[0023] Furthermore, the chemical composition and weight percentage of the cold-rolled automotive steel are: C: 0.002-0.080%, Si: 0.01-0.05%, Mn: 0.01-0.06%, P≤0.030%, S≤0.025%, Alt: 0.010-0.030%, Ti: 0.02-0.10%, Nb: 0.02-0.10%, and the balance is Fe and unavoidable impurities.

[0024] Further, the flame cleaning thickness is 5.0 cm.

[0025] Furthermore, the chemical composition and weight percentage of the cold-rolled automobile steel are: C: 0.040%, Si: 0.02%, Mn: 0.06%, P: 0.015%, S: 0.017%, Alt: 0.015%, Ti: 0.02%, Nb: 0.04%, and the balance is Fe and unavoidable impurities.

[0026] Furthermore, the chemical composition and weight percentage of the cold-rolled automobile steel are: C: 0.030%, Si: 0.02%, Mn: 0.03%, P: 0.023%, S: 0.004%, Alt: 0.024%, Ti: 0.05%, Nb: 0.04%, and the balance is Fe and unavoidable impurities.

[0027] Furthermore, the chemical composition and weight percentage of the cold-rolled automotive steel are: C: 0.042%, Si: 0.01%, Mn: 0.02%, P: 0.012%, S: 0.013%, Alt: 0.012%, Ti: 0.03%, Nb: 0.06%, and the balance is Fe and unavoidable impurities.

[0028] Furthermore, the chemical composition and weight percentage of the cold-rolled automotive steel are: C: 0.008%, Si: 0.04%, Mn: 0.05%, P: 0.017%, S: 0.018%, Alt: 0.020%, Ti: 0.07%, Nb: 0.02%, and the balance is Fe and unavoidable impurities.

[0029] Compared with the prior art, the beneficial technical effects of the present invention are:

[0030] The present invention regulates the chemical composition design, removal of oxides on the surface of the ingot, control of surface residues in the cold rolling state, type of work rolls produced, surface micromorphology characterization parameters, amount of oiling, time interval from oiling to fluorozirconate-silanization, surface defects and rust point control, number and area of ​​oxide inclusions, degreasing effect, etc., to improve the surface quality of the steel plate. There are many factors that affect the fluorozirconate-silane film on the surface of the cold-rolled plate. It is impossible to prepare a high-quality fluorozirconate-silane film by simply controlling the grain size, surface roughness and other characteristics. Therefore, the present application limits the cleaning of the slab surface before hot rolling to ensure that the substrate surface has a high degree of cleanliness and less residues, avoid the enrichment of harmful elements on the substrate surface, and then improve the quality of the fluorozirconate-silane film on the surface of the automobile plate; in order to ensure the degreasing and cleaning effect, the present invention limits the amount of oiling on the strip surface and the time interval from oiling to fluorozirconate-silanization, further improving the quality of the fluorozirconate-silane film on the automobile plate.

[0031] The present invention provides a method for improving the quality of a cold-rolled sheet fluorozirconate-silane film. The fluorozirconate-silane film has uniform thickness, complete coverage, and a dense structure, which makes organizational preparations for a subsequent electrophoresis process and improves the corrosion resistance of the electrophoretic paint film. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The present invention will be further described below in conjunction with the accompanying drawings.

[0033] Figure 1 The morphology of the fluorozirconate-silane film in Example 1;

[0034] Figure 2 The morphology and energy spectrum of the fluorozirconate-silane film of Comparative Example 1;

[0035] Figure 3 This is the morphology of the fluorozirconate-silane film of Comparative Example 2;

[0036] Figure 4 This is the morphology of the fluorozirconate-silane film of comparative example 3. DETAILED DESCRIPTION

[0037] A method for improving the quality of a cold-rolled sheet fluorozirconate-silane film, specifically comprising:

[0038] (1) The chemical composition and weight percentage of cold-rolled automobile steel are C: 0.002-0.080%, Si: 0.01-0.05%, Mn: 0.01-0.06%, P≤0.030%, S≤0.025%, Alt: 0.010-0.030%, Ti: 0.02-0.10%, Nb: 0.02-0.10%, and the balance is Fe and unavoidable impurities.

[0039] (2) For the production of cold-rolled automobile steel, the surface of the continuous casting billet is flame cleaned and then heated in the furnace. The flame cleaning thickness is 4.0-6.0 cm. The total amount of residue (residual oil + residual iron) on the surface of the cold-rolled cold-hardened strip after pickling is ≤200 mg / m 2 , chrome-plated rollers are used for annealing and leveling.

[0040] (3) Surface morphology characteristic parameters of cold-rolled automotive steel: roughness Ra is 0.7-1.1 μm, peak density RPc value is 90-140, surface maximum profile peak height Sp is 2.5-3.5 μm, while ensuring that the skewness Ssk is -0.6-0.2, the steepness Sku is 1.5-2.5, the root mean square slope Sdq is 0.35-0.40, the surface area growth rate Sdr% is 4.0-5.5, the surface area ratio is ≥1.05, and the strip surface oil coating amount is 600-1000 mg / m 2 .

[0041] (4) The time interval from oiling to fluorozirconate-silanization is ≤ 50 days.

[0042] (5) Before fluorozirconate-silanization, the surface of the cold-rolled sheet was inspected to find no scratches or rust spots visible to the naked eye within an area of ​​70 cm × 150 cm.

[0043] (6) Before fluorozirconate-silanization, the surface of the cold-rolled sheet was examined by scanning electron microscopy. Within an area of ​​70 cm × 150 cm, the number of oxide inclusions was ≤ 5, and the inclusion area was ≤ 5 × 5 μm 2 .

[0044] (7) Fully degrease before fluorozirconate-silane to ensure that the surface of the cold-rolled sheet is completely exposed and fully covered with water film.

[0045] The present invention is described in detail below through specific examples. The examples are intended to help understand the present invention but are not intended to limit the present invention.

[0046] Example 1 and Comparative Examples 1, 2, and 3 mainly investigate the effects of the flame cleaning thickness of the ingot surface, the number of oxide inclusions, and the inclusion area on the quality of the cold-rolled sheet fluorozirconate-silane.

[0047] Table 1 Flame cleaning thickness (cm) of the ingot surface and the total amount of residue on the surface of the cold hardened strip (mg / m 2 )

[0048]

[0049] Table 2 Surface morphology characteristic parameters of Example 1 of the present invention and Comparative Examples 1-3

[0050]

[0051] Table 3 Surface oil coating amount (mg / m 2 ), the time interval from oiling to fluorozirconate-silanization (days), whether there are visible scratches and rust spots on the surface, the number of surface oxidation inclusions (pieces), the area of ​​inclusions (μm 2 ) Whether the degreasing is complete

[0052]

[0053]

[0054] It can be seen from Comparative Example 1 that the thickness of the flame cleaning on the surface of the cold-rolled ingot has an effect on the fluorozirconate-silane. When the cleaning thickness is 3.0 cm, the billet is subjected to hot rolling, pickling, continuous annealing and other processes, and the surface of the cold-rolled sheet is tested after the fluorozirconate-silane treatment. Residual iron oxide inclusions exist on the surface of the cold-rolled sheet. The surface iron oxide inclusions cannot be completely covered, and most of them are exposed in the fluorozirconate-silane film. The surface inclusions have strong heredity. Although the subsequent electrophoretic paint can cover the inclusions, the bonding force is reduced, and blistering is prone to occur during the corrosion resistance evaluation.

[0055] It can be seen from Comparative Example 2 that the number of inclusions on the surface of the cold-rolled sheet has an impact on the quality of the fluorozirconate-silane film. It will affect the integrity and continuity of the fluorozirconate-silane film. The characteristics of the inclusions are generally non-conductive non-metallic. During the fluorozirconate-silane process, the electrode potential of this area is different from that of other normal areas, which affects the adsorption of oligomers and the matrix when the fluorozirconate-silane film is formed.

[0056] From Comparative Example 3, it can be seen that there are single large inclusions on the surface of the cold-rolled sheet. When the area exceeds 6×8 μm 2 When the inclusions are present, the integrity and continuity of the fluorozirconate-silane film will be affected. The characteristics of the inclusions are generally non-conductive non-metallic. During the fluorozirconate-silanization process, the electrode potential of this area is different from that of other normal areas, which affects the adsorption of oligomers and the matrix when the fluorozirconate-silane film is formed.

[0057] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for improving the quality of a cold-rolled sheet fluorozirconate-silane film, characterized in that: include: Used for flame cleaning of the surface of continuous casting billet for cold-rolled automobile steel and then heating in furnace. The flame cleaning thickness is 4.0-6.0cm. The total amount of residue on the surface of cold-rolled cold-hardened strip after pickling is ≤200mg / m 2 , chrome-plated rollers are used for annealing and leveling; Surface morphology characteristic parameters of cold-rolled automotive steel: roughness Ra is 0.7-1.1μm, peak density RPc value is 90-140, surface maximum profile peak height Sp is 2.5-3.5μm, while ensuring that the skewness Ssk is -0.6-0.2, the steepness Sku is 1.5-2.5, the root mean square slope Sdq is 0.35-0.40, the surface area growth rate Sdr% is 4.0-5.5, the surface area ratio is ≥1.05, and the strip surface oil coating amount is 600-1000mg / m 2 ; The time interval from oiling to fluorozirconate-silanization is ≤ 50 days; Before fluorozirconate-silanization, the surface of the cold-rolled sheet was checked to find no scratches or rust spots visible to the naked eye within an area of ​​70 cm × 150 cm; The surface of the cold-rolled sheet was examined by scanning electron microscopy before fluorozirconate-silanization. Within an area of ​​70 cm × 150 cm, the number of oxide inclusions was ≤ 5, and the inclusion area was ≤ 5 × 5 μm. 2 ; Before fluorozirconate-silane, sufficient degreasing is carried out to ensure that the surface of the cold-rolled plate is completely exposed and the water film is fully covered.

2. The method for improving the quality of the fluorozirconate-silane film of cold-rolled sheet according to claim 1, characterized in that: The chemical composition and weight percentage of the cold-rolled automobile steel are: C: 0.002-0.080%, Si: 0.01-0.05%, Mn: 0.01-0.06%, P≤0.030%, S≤0.025%, Alt: 0.010-0.030%, Ti: 0.02-0.10%, Nb: 0.02-0.10%, and the balance is Fe and unavoidable impurities.

3. The method for improving the quality of the cold-rolled sheet fluorozirconate-silane film according to claim 1, characterized in that: The flame cleaning thickness is 5.0 cm.

4. The method for improving the quality of the cold-rolled sheet fluorozirconate-silane film according to claim 2, characterized in that: The chemical composition and weight percentage of the cold-rolled automobile steel are as follows: C: 0.040%, Si: 0.02%, Mn: 0.06%, P: 0.015%, S: 0.017%, Alt: 0.015%, Ti: 0.02%, Nb: 0.04%, and the balance is Fe and inevitable impurities.

5. The method for improving the quality of the fluorozirconate-silane film of cold-rolled sheet according to claim 2, characterized in that: The chemical composition and weight percentage of the cold-rolled automobile steel are: C: 0.030%, Si: 0.02%, Mn: 0.03%, P: 0.023%, S: 0.004%, Alt: 0.024%, Ti: 0.05%, Nb: 0.04%, and the balance is Fe and unavoidable impurities.

6. The method for improving the quality of the fluorozirconate-silane film of cold-rolled sheet according to claim 2, characterized in that: The chemical composition and weight percentage of the cold-rolled automobile steel are: C: 0.042%, Si: 0.01%, Mn: 0.02%, P: 0.012%, S: 0.013%, Alt: 0.012%, Ti: 0.03%, Nb: 0.06%, and the balance is Fe and unavoidable impurities.

7. The method for improving the quality of the fluorozirconate-silane film of cold-rolled sheet according to claim 2, characterized in that: The chemical composition and weight percentage of the cold-rolled automobile steel are: C: 0.008%, Si: 0.04%, Mn: 0.05%, P: 0.017%, S: 0.018%, Alt: 0.020%, Ti: 0.07%, Nb: 0.02%, and the balance is Fe and unavoidable impurities.

Citation Information

Patent Citations

  • Control method for increasing painting performance and surface quality of cold rolling automobile sheet

    CN105420607A